Viola betonicifolia-Mediated Biosynthesis of Silver Nanoparticles for Improved Biomedical Applications - Jang, Yingping; Zhang, Xiaoya; Zhu, Rongxue; Li, Songlin; Sun, Shiyu; Li, Wenqiang; Liu, Hao (Frontiers in Microbiology, 2022)
We report the biosynthesis of silver (Ag) nanoparticles (NAPs) (LEVB-Ag NAPs) by an environmentally friendly green synthesis approach using the phytoconstituents of Viola betonicifolia leaf extract. The spectroscopic techniques were employed to characterize biosynthesized LEVB-Ag NAPs successfully. Biosynthesized LEVB-Ag NAPs were assessed for antibacterial and antimycotic activities against bacterium and mycological strains (H. pylori, S. epidermidis, C. tropicalis, and T. rubrum) using the serial dilution method. They were also evaluated for their biofilm inhibiting potential against both bacterial and fungi species. They were further assessed for the cytobiocompatible potential with two normal cell lines (293T and hMSC). The results demonstrate that the biosynthesized LEVB-Ag NAPs showed superior log10 reduction in bacterial and fungal growth and presented more than 99.50% killing efficiency. Moreover, biosynthesized LEVB-Ag NAPs excellently inhibited the biofilm formation of bacterial (Gram-positive and Gram-negative) and mycological strains and presented more than 80% biofilm inhibiting percentage compared to both plant extract and CHE-Ag NAPs. They further presented good cytobiocompatibility in vitro with 293T and hMSC cells compared to CHE-Ag NAPs. Biosynthesized LEVB-Ag NAPs presented superior antibacterial, antimycotic, biofilm inhibition, and cytobiocompatible results that might be attributed to the synergistic effect of the NAPs' physiochemical properties and the immobilized phytoconstituents from plant leaf extract on their surface. Hence, biosynthesized LEVB-Ag NAPs may be a promising contender for a variety of therapeutic applications.